2022
DOI: 10.1111/evo.14592
|View full text |Cite
|
Sign up to set email alerts
|

Diverge and Conquer: Phylogenomics of southern Wallacean forest skinks (Genus:Sphenomorphus) and their colonization of the Lesser Sunda Archipelago

Abstract: Transcriptome Sequencing: RNA was extracted from three Sphenomorphus samples including S. striolatus (Flores, MVZ293137) and S. melanopogon from Sumbawa (MVZ293067) and Lembata (MVZ292954) using the RNEasy Protect Mini Kit (Qiagen) and provided protocol.RNA extractions were evaluated using a BioAnalyzer 2100 RNA Pico chip (Agilent). Sequencing libraries were prepared with half reactions of the TruSeq RNA Library Preparation Kit V2 (Illumina), starting with Poly-A selection for samples with high RIN scores (> 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 133 publications
1
7
0
Order By: Relevance
“…Developments in bioinformatic software have further enabled utilization of bycatch data, for example to detect copy number variation (Kuilman et al 2015 ; Laver et al 2022 ) from unmapped DNA and RNA reads (Zhang et al 2016 ; Gasc et al 2016 ; Laine et al 2019 )—including from public data (Vieira and Prosdocimi 2019 ). Collectively, this work demonstrates the value (and quality; Guo et al 2012 ) of sequence data derived from outside targeted regions, and its use for examining a variety of evolutionary questions is growing (e.g., Derkarabetian et al 2019 ; Ballesteros et al 2020 ; Reilly et al 2022 ; Zozaya et al 2022 ). However, while the effects of missing data in studies employing phylogenetic inference have been examined (both generally, and in the context of sequence capture; see Tilston Smith et al 2020 , and references therein), its effects on population genetic and phylodynamic analyses—particularly when the data is bycatch and therefore more likely to be patchy in nature—have received less focus.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Developments in bioinformatic software have further enabled utilization of bycatch data, for example to detect copy number variation (Kuilman et al 2015 ; Laver et al 2022 ) from unmapped DNA and RNA reads (Zhang et al 2016 ; Gasc et al 2016 ; Laine et al 2019 )—including from public data (Vieira and Prosdocimi 2019 ). Collectively, this work demonstrates the value (and quality; Guo et al 2012 ) of sequence data derived from outside targeted regions, and its use for examining a variety of evolutionary questions is growing (e.g., Derkarabetian et al 2019 ; Ballesteros et al 2020 ; Reilly et al 2022 ; Zozaya et al 2022 ). However, while the effects of missing data in studies employing phylogenetic inference have been examined (both generally, and in the context of sequence capture; see Tilston Smith et al 2020 , and references therein), its effects on population genetic and phylodynamic analyses—particularly when the data is bycatch and therefore more likely to be patchy in nature—have received less focus.…”
Section: Introductionmentioning
confidence: 83%
“…For example, in previous human research, high-quality SNPs from outside target regions bolstered tested datasets by up to 461% (Guo et al 2012 ). Indeed, this is a growing field (e.g., Derkarabetian et al 2019 ; Ballesteros et al 2020 ; Granados Mendoza et al 2020 ; Sanderson et al 2020 ; Costa et al 2021 ; Reilly et al 2022 ; Zozaya et al 2022 ), and we recommend that more researchers consider the extraction and analysis of bycatch data (as well as other off-target genomic resources, such as unmapped RNA reads in transcriptomic studies), in their informatics pipelines. Although some of these data will undoubtedly represent contamination and/or poor quality sequences, what remains may provide the raw material for new avenues of active research (Samuels et al 2013 ; Griffin et al 2014 ; Seaby et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an over-water dispersal might be the most likely dispersal scenario into Sulawesi. Many species, such as terrestrial Sphenomorphus skinks 104 , Draco lizards 105 , Cyrtodactylus geckos 106 , and frogs in the genus Limonectes 96 have been suggested to have dispersed between islands on the Lesser Sunda Arc (Lombok, Sumbawa, Komodo, Flores, and Lembata). However, although our phased concatenated tree supports a Southwest colonization of Sulawesi (likely from Selayar Island, for which samples here cluster with those of the Southwest Peninsula), a southern dispersal from the Lesser Sunda Islands is considered improbable pending the discovery of Hypsiscopus from these islands.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genetic studies revealed that a number of wide-ranging reptile and amphibian species from the region documented solely based on morphology (e.g. Kaiser et al 2011;O'Shea et al 2012) actually comprise multiple species with localised distributions (Reilly et al 2019a(Reilly et al , 2022a(Reilly et al , 2022b(Reilly et al , 2022c(Reilly et al , 2023, suggesting that true herpetofaunal diversity of the region is underestimated.…”
Section: Introductionmentioning
confidence: 99%